2022
DOI: 10.3389/fonc.2022.1039888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autologous hematopoietic stem cell transplantation for patients with peripheral T-cell lymphoma in China: A propensity score-matched analysis

Abstract: BackgroundThe role of consolidation therapy with autologous stem cell transplantation (ASCT) in patients with peripheral T-cell lymphoma (PTCL) in first complete remission (CR1) or partial remission (PR1) remains controversial. The existing data from China are limited. Therefore, we aimed to investigate the effect of ASCT on the survival of Chinese patients with PTCL showing response to induction chemotherapy at our hospital.MethodsWe retrospectively reviewed the data of patients with PTCL (excluding Natural k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
(59 reference statements)
2
5
0
Order By: Relevance
“…Prior studies also reported this survival advantage for AITL patients receiving ASCT. 10,11 However, we observed a 28.2% relapse rate in AITL patients after ASCT. Epperla et al 19 reported that allo-HCT can offer durable disease control for AITL patients who relapse after ASCT.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Prior studies also reported this survival advantage for AITL patients receiving ASCT. 10,11 However, we observed a 28.2% relapse rate in AITL patients after ASCT. Epperla et al 19 reported that allo-HCT can offer durable disease control for AITL patients who relapse after ASCT.…”
Section: Discussionmentioning
confidence: 58%
“…suggested only AITL patients benefit from ASCT. However, most of these studies did not compare ASCT and non‐ASCT in the CR subgroup 11,16 . Here, we observed that among TCL patients achieving CR after first‐line treatment, non‐ALCL patients benefit from ASCT compared to chemotherapy, while outcomes remain comparable for the ALCL group.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations